The effect of rare earth on the radiation shielding properties of transparent lead-free Alumino-borophosphate glass system. (April 2022) - Suresh, A. Antony; Vinothkumar, P.; Mohapatra, Manoj; Dhavamurthy, M.; Murugasen, Priya
Abstract: The nuclear radiation shielding properties for Alumino-borophosphate (ABP) glass system with different rare earth dopants were studied. The mass attenuation coefficient (μ/ρ) values of different glass were calculated by Phy-X software for the photon energies in the energy range from 1 keV to 100 GeV. The Gamma-ray attenuation parameters such as effective atomic numbers (Zeff ), half value layer (HVL), mean free path (MFP), mass attenuation coefficients (MAC) and tenth value layer (TVL) was determined by μ/ρ values. Exposure build up factors (EBF) and energy absorption build up factors (EABF) are determined by using the G-P fitting method in relation to penetration depth and the incident photon energy. In addition, the neutron radiation shielding parameters was computed and compared with conventional neutron shielding materials. The outcomes from the present investigation explore the advantages of the ABP glasses in different shielding applications. Highlights: ABP-Dy glass has the lowest HVL, TVL, and MFP. ABP glasses have comparable EBF values with conventional shielding material. ABP-Dy glass possesses high FNRCS values. ABP-Dy glass is more promising for radiation (proton, fast neutron) shielding.